Impact of learning design in technology integration: the effort to improve literacy culture of widyaiswara at Pusdiklat BSSN - Firman Suprijandoko (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2020)
This research is a series of studies on the big theme of Smart-Pusdiklat at the BSSN environment. The research question revealed was how to improve the culture of BSSN Widyaiswaras’ literacy through meaningful learning whose technological scope could maintain the perspective of constructivist approaches to learning. The researcher discusses 2 (two) parts of the Learning Design, namely Technology Skills, and Meaningful Learning, in using integrated technology applications. Considering the limitations of digital exploration on the side of Widyaiswara, the literacy culture of fellow Widyaiswara becomes significant to maintain the gap. This research used exploratory research methods with a qualitative approach. This method is intended to explore a new phenomenon that may not have been studied before. This is the novelty value of this research. The application used in this study was Slack Workspace, which is integrated with 4 (four) other applications, namely Trello for Slack, Google Drive for Slack, Google Calendar for Slack, and Zoom for Slack. The specific results of this study were revealed that the Learning Design is focused on teaching technology skills, and meaningful learning to Widyaiswara. Also, by being involved in the learning experiences which are active, intentional, authentic, constructive, and cooperative.